The effects of pH on phosphate uptake from the soil - Barrow, N. J. (Plant and soil, 2017)
Near neutral pH values are widely thought to be optimum for uptake of phosphate. This belief is based on an outdated view of soil phosphate chemistry. The literature on uptake by plants from solution and from soil, and especially on desorption by soil, are all consistent with a much lower pH optimum.